2021
DOI: 10.1039/d1cc01578h
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient electrocatalysts for overall water splitting: mesoporous CoS/MoS2 with hetero-interfaces

Abstract: A mesoporous CoS/MoS2 with abundant heterogeneous interfaces was facile synthesized from bimetallic hybrid zeolitic imidazolate framework, which showed excellent catalytic activity and reaction kinetics on both HER and OER in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…8 Huang et al developed mesoporous CoS/MoS 2 heterointerfaces and reported a good OER activity of 281 mV ( η 10 ). 21 The above comparison justifies that the material in the present report, Ni d (5)S v @ReS 2 NS, provides a simple wet-chemical development process and shows promising OER activity. It is well established that the OER proceeds through four consecutive reaction steps, and the metal centres mostly act as the active sites.…”
supporting
confidence: 76%
“…8 Huang et al developed mesoporous CoS/MoS 2 heterointerfaces and reported a good OER activity of 281 mV ( η 10 ). 21 The above comparison justifies that the material in the present report, Ni d (5)S v @ReS 2 NS, provides a simple wet-chemical development process and shows promising OER activity. It is well established that the OER proceeds through four consecutive reaction steps, and the metal centres mostly act as the active sites.…”
supporting
confidence: 76%
“…Lower charge-transfer resistance for CdS@Ni has been confirmed by the evidence that a smaller arch is detected. [53][54][55][56] Photo-irradiation can further decrease the arc diameter, suggesting that the isolated Ni atoms act as electron collectors to facilitate the separation of photogenerated electron-hole pairs on the CdS@Ni interface. Thus, an adequate supply of electrons is realized by isolated Ni atoms, optimizing the elementary process of photocatalytic hydrogen evolution.…”
Section: Mechanism Explorationmentioning
confidence: 99%
“…12 In particular, cobalt sulfides incorporated into MoS 2 have been widely explored. For example, recently Huang et al have synthesised mesoporous CoS/MoS 2 for water splitting application, 13 Ganesan et al have created a multi-shelled CoS 2 -MoS 2 hollow sphere for efficient water splitting, 14 and Guo et al have assembled a core-shell Co 3 S 4 @MoS 2 for both the HER and OER. 15 Besides introducing cobalt into MoS 2 , the electrochemical efficiency of the electrocatalysts can be strategically promoted by active site engineering strategies, including edge-site formation, nano-sized TMD and highly curved structures formed on the MoS 2 crystals.…”
Section: Introductionmentioning
confidence: 99%